Polybrominated diphenyl ethers and alternative halogenated flame retardants in mangrove plants from Futian National Nature Reserve of Shenzhen City, South China. (May 2020) - Hu, Yongxia; Sun, Yuxin; Pei, Nancai; Zhang, Zaiwang; Li, Huawei; Wang, Weiwei; Xie, Jinli; Xu, Xiangrong; Luo, Xiaojun; Mai, Bixian
Abstract: Halogenated flame retardants (HFRs) are ubiquitous in the environment, but little information is available about the bioaccumulation of HFRs in mangrove plants. In this study, three mangrove plant species were collected from Futian National Nature Reserve of Shenzhen City, South China to investigate the bioaccumulation of polybrominated diphenyl ethers (PBDEs) and several alternative halogenated flame retardants (AHFRs), including decabromodiphenyl ethane (DBDPE), 1, 2-bis(2, 4, 6-tribromophenoxy)ethane (BTBPE), hexabromobenzene (HBB), pentabromotoluene (PBT), tetrabromop-xylene ( p TBX), pentabromoethylbenzene (PBEB) and dechlorane plus (DP). The mean concentrations of PBDEs, DBDPE, BTBPE, p TBX, PBT, PBEB, HBB and DP in mangrove plant species were 2010, 1870, 36.2, 18.7, 40.1, 17.8, 9.68 and 120 pg g −1 dry weight, respectively. PBDEs were the dominant HFRs in mangrove plant tissues, followed by DBDPE. The relative abundance of BDE 209 in three mangrove plant tissues were much lower than those in sediments. Significant negative relationships between log root bioaccumulation factors and log K ow, and between log TFr-s (from root to stem) and log K ow were observed, indicating that HFRs with low hydrophobicity were easily absorbed by mangrove roots and stems. A positive correlation between log TFs-l (from stem to leaf) and log K ow were found, suggesting that air-leaf exchange may occur in mangrove plants. This study highlights the uptake of HFRs by mangrove plants, which can be used as remediation for HFRs contamination in the environment. Graphical abstract: Image 1 Highlights: PBDEs and AHFRs were determined in natural mangrove sediments and plants. PBDEs were the dominant HFRs in mangrove plant tissues, followed by DBDPE. The root accumulation factor was regulated by log K ow of PBDEs and AHFRs. Translocation of PBDEs and AHFRs from root to stem positively correlated with log K ow . Mangroves are playing important roles in retaining PBDEs and AHFRs.